2021
DOI: 10.1111/pedi.13156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deprivation on glycaemic control in youth with type 1 diabetes in the southwestern region of France

Abstract: Objectives The objective of this multicenter cross‐sectional study was to determine predictors of poor glycaemic control in children with type 1 diabetes mellitus (T1DM), particularly with respect to socioeconomic status (SES). Methods Our study population consisted of 1154 children who attended T1DM follow‐up consultation with a pediatric diabetes specialist. Clinical and demographic data were retrieved retrospectively from patients' records. Individual deprivation was defined by an EPICES (Evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Alternatively, the current study may have lacked adequate statistical power, or the follow-up time may have been insufficient. Similar to our findings, some studies showed that area-level deprivation was associated with long-term HbA1c levels [6,8,9,11]. The French study cited above revealed a significant association between HbA1c levels and the EDI quintiles, but the EDI did not reflect glycemic control in a manner consistent with the EPICES score [11].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Alternatively, the current study may have lacked adequate statistical power, or the follow-up time may have been insufficient. Similar to our findings, some studies showed that area-level deprivation was associated with long-term HbA1c levels [6,8,9,11]. The French study cited above revealed a significant association between HbA1c levels and the EDI quintiles, but the EDI did not reflect glycemic control in a manner consistent with the EPICES score [11].…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have shown that individual social deprivation is associated with longer-term glycemic control [2][3][4][5]11]. One French study showed that the mean HbA1c level measured at follow-up visits > 1 year after T1D diagnosis was 43% higher in children/adolescents with EPICES scores ≥ 30.17, compared with children/adolescents who had lower scores (P <0:001) [11]. However, we found no association between the EPICES score and the HbA1c trajectory > 4 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study running from 2017 to 2018 found no association of deprivation with CGM utilization, concluded to be due to the pervasiveness of the health insurance system. 46 …”
Section: Current Situationmentioning
confidence: 99%
“…In Germany, France, and Australia, the inclusion of CGMs in universal healthcare plans correlated with large increases in usage, predominantly among those of lower SES. 34 , 44 , 46 In California, generous is-CGM reimbursement practices for their Medicaid recipients impacted disparities to such a degree that no significant differences in CGM utilization were found among the various ethnicities. 66 …”
Section: The Influences Of Ses Social Context and Ethnicitymentioning
confidence: 99%